Identification of circular RNAs hsa_circ_0044235 in peripheral blood as novel biomarkers for rheumatoid arthritis. (23rd September 2018) - Luo, Q; Zhang, L; Li, X; Fu, B; Deng, Z; Qing, C; Su, R; Xu, J; Guo, Y; Huang, Z; Li, J
Summary: Circular RNAs (circRNAs) are a new class of RNAs that can be used as biomarkers in clinical blood samples. However, little is known about circRNAs' diagnostic values for rheumatoid arthritis (RA). In this study, the hsa_circ_0054189, hsa_circ_0008675, hsa_circ_0082689, hsa_circ_0082688, hsa_circ_0010932, hsa_circ_0002473 and hsa_circ_0044235 in peripheral blood were determined by quantitative reverse transcription–polymerase chain reaction (qRT–PCR). For hsa_circ_0044235, only one abnormal expression circRNAs in peripheral blood was selected as a targeted circRNA to explore the diagnostic value for RA. Our work demonstrated that the hsa_circ_0044235 in peripheral blood was decreased significantly in RA patients. The hsa_circ_0044235 in peripheral blood from RA patients did not correlate with C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPA) or disease activity score 28 (DAS28). Receiver operating characteristic (ROC) curve analysis suggested that the hsa_circ_0044235 in peripheral blood has significant value in the diagnosis of RA. The risk score based on hsa_circ_0044235 in peripheral blood also distinguished significantly the patients with RA from systemic lupus erythematosus (SLE). This study suggests that the hsa_circ_0044235 in peripheral blood may be a potential biomarker of patients with RA. Graphical Abstract: